Estimativa de subnotificação de casos de AIDS em Fortaleza, Ceará – 2002 e 2003 : uma aplicação da técnica de captura-recaptura - Gonçalves, Valéria Freire (2006)
Underreporting is one of the major problems challenging epidemiologic AIDS surveillance. The objective of this study was to estimate the level of underreporting of AIDS in adults in Fortaleza in the period 2002-2003 using the capture-recapture method. In addition, the level of underreporting at two hospitals for AIDS referral (Hospital São José – HSJ, and Hospital Geral de Fortaleza – HGF was estimated. The study relied on three secondary databases: SINAN (national disease surveillance), SISCEL (laboratory test control) and SIM (mortality information). The systems were compared and cases confirmed by SINAN were considered as reported. Cases from the two databases were paired using the software RecLink II. Subsequently cases eligible for the capture-recapture method were selected using the Lincoln-Petersen and Chapmam estimators. The levels of underreporting were estimated at 33.1% and 14.1% for SISCEL and SIM, respectively. Underreporting for SISCEL was 5.4% at HSJ and 90.5% at HGF. The study shows a considerable level of underreporting of AIDS cases in Fortaleza for the period 2002-2003 and suggests that SISCEL is an important source of AIDS reporting considering that it allowed to detect levels of underreporting more than twice the estimates derived from the sources SIM and SINAN. The level of underreporting was considerably higher at HF than at HSJ. The software RecLink II was shown to be a practical tool for identifying cases not reported to SINAN. The capture-recapture method is a simple, time-saving and inexpensive way to compare two systems when necessary. Considering the findings of the present study, SINAN-AIDS should be compared monthly with all relevant information systems in order to reduce levels of AIDS underreporting.